Modulations of Identities: A Regional Façade Design Resource from the Classicalised (Aristocratic) Vernacular - Puteri Shireen Jahn Kassim; Noorhanita Abdul Majid; Norwina Mohd Nawawi; Tengku Anis Qarihah (Cultural Syndrome, 2019)
The paper discusses and describes a range of templates, models and variations of  tropicalised modulation of facades and recesses from in the local vernacular which convey an aesthetic sense of the region, to counter the homogeneity of modern facades. These range of identified Malay-Nusantara are abstracted from elevations of mansions and palaces which convey a sense of the Classical and which were identified as a new identified substyle of the vernacular. Operationally categorised as a form of Classical vernacular, they represent a rich range of models and templates arising from the region’s past ingenuities that can also transcend the present approach of merely adorining modern structures with Nusantara roofs into a more critical approach. The paper argues that these variations can constitue an untapped resources for creating the modulations of facades in any  Nusantara-themes city of the future; without reverting to cosmetic application of motifs and cut-and -paste from the vernacular  This language includes key attributes such as proportioned and regular spaces of columns, recesses, projections, staircases and balustrades  which are fused in various ways  to present a more  critical trope  of local  identity that can be combined and permutate into a tropical ‘facadism’ with a differentiated and  dirinctive identity for the south east Asia city in general  and the Malay nusantara in particular.